Innovation in Health Learning Management for Stunting-Vulnerable Communities in Sub-Urban Areas - Fien Lolong, Rima; Adolfien Katuuk, Deitje; Rawis, Joulanda; S. J. Lengkong, Jefry (International Journal of Social Service and Research, 2025)
Stunting remains a major public health challenge in Indonesia, particularly in sub-urban areas characterized by limited access to education, health services, and socio-economic resources. This study aims to analyze innovations in health learning management for stunting-vulnerable communities in sub-urban areas, with a focus on East Bolaang Mongondow Regency. Using a qualitative research approach, data were collected through in-depth interviews with heads of community health centers and health promotion officers, field observations, and document analysis. The findings reveal that health learning management innovations are implemented through four managerial functions: planning, organizing, implementation, and evaluation. Planning is based on local stunting data and community needs; organizing emphasizes family- and community-based learning networks; implementation applies participatory and experiential learning strategies; and evaluation is conducted through participatory and family-based monitoring. These innovations demonstrate that context-based and community-embedded health learning management can effectively support behavioral change and strengthen stunting prevention efforts in sub-urban communities.